Psychiatric morbidity in married females living away from their spouses attending the psychiatry clinic in a tertiary care, teaching hospital - Baig, Mirza Ghazanfar; ., Baderuzzaman; Athar, Fahim; Ahmed, Arifuddin; ., Matin; Ramakrishna, P. (International Journal of Research in Medical Sciences, 2017)
Background: In India economic problems like dowry and related issues play a major role in the problems of marriage and separation The aim of the present study is to assess the psychological impact on married females who living away from their spouses, and comparison of the psychiatric morbidity with the married women who are living with their spouses. Methods: A total of 35 subjects were included in the study. Intake proforma was specially designed for study and the questions were divided into 4 subscales (somatic complaints anxiety/insomnia social dysfunction and severe depression). Results: The study clearly revealed that the occupational separation has a significant negative impact on the marital quality of the women spouses of men working abroad or living away. Comparison with the marital quality of the control group, the group does not have the separation; the study group differs significantly in marital quality. The factors such as social support from family and friends, the stay of the study group with parents or in-laws, and duration of pre-separation, the study proved that there is no significant difference exists on the marital quality of the study group based on these factors. Conclusions: The numbers of females who were separated from their spouses are more likely to have psychiatric illnesses due the additional work load of looking after the children and managing the household activities. The study also found that the females staying with their parents after the separation from their spouses were less likely to have a severe psychiatric morbidity as they felt comfortable due the cooperation from their parents.